STOP 301: A Phase 3, open‐label study of safety, tolerability, and exploratory efficacy of INP104, Precision Olfactory Delivery (POD®) of dihydroergotamine mesylate, over 24/52 weeks in acute treatment of migraine attacks in adult patients. Issue 8 (7th August 2021) - Smith, Timothy R.; Winner, Paul; Aurora, Sheena K.; Jeleva, Maria; Hocevar‐Trnka, Jasna; Shrewsbury, Stephen B.
Abstract: Objective: To report the safety, tolerability, exploratory efficacy, and patient acceptability of INP104 for the acute treatment of migraine from the Phase 3 STOP 301 trial. Background: Dihydroergotamine (DHE) has long been used to treat migraine, but intravenous administration is invasive, frequently associated with adverse events (AEs), and not suitable for at‐home administration. INP104 is an investigational drug device that delivers DHE mesylate to the upper nasal space using a Precision Olfactory Delivery technology and was developed to overcome the shortcomings of available DHE products. Methods: STOP 301 was an open‐label, 24‐week safety study, with a 28‐week extension period. After a 28‐day screening period where patients used their "best usual care" to treat migraine attacks, patients were given INP104 (1.45 mg) to self‐administer nasally with self‐recognized attacks. The primary objective of this study was to assess safety and tolerability, with a specific focus on nasal mucosa and olfactory function. Exploratory objectives included efficacy assessments of migraine measures and a patient acceptability questionnaire. Results: A total of 360 patients entered the 24‐week treatment period, with 354 patients dosing at least once. INP104‐related treatment‐emergent AEs were reported by 36.7% (130/354) of patients, and 6.8% (24/354) discontinued treatment due to AEs over 24 weeks. No new safety signals were observed following delivery to the upper nasal space. Pain freedom, the most bothersome symptom freedom, and pain relief at 2 h post‐INP104 were self‐reported by 38.0% (126/332), 52.1% (173/332), and 66.3% (167/252) of patients, respectively. A low recurrence rate at 24 and 48 h was observed (7.1% [9/126] and 14.3% [18/126], respectively). Most patients found INP104 easy to use and preferred it over their current therapy. Conclusions: INP104 has the potential to deliver rapid symptom relief, without injection, that is well tolerated and suitable for outpatient use. Results suggest INP104 may be a promising treatment for patients with migraine.